DISCOVERING STUDENTS’ ABILITY IN PRONUNCING TWO SYLLABLE ENGLISH WORDS - Rivieka, Farel Akbar; Aruan, Rumiri; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Pronunciation ability is a crucial aspect of language learning. Thecapability to articulate words correctly significantly influences comprehension andcommunication in the target language. The aim of this study is to find out the ability ofeight grade student of SMPN 1 Kampar ability in pronouncing English words thatconsist of two syllables, which consists of 23 students in total. The writer used clusterrandom sampling technique to determine the sample. The samples were 23 students.The instrument was a test which consisted of 50 items. The frame of the test consist of knowledge test by using cassete and sound system. The student will listed to 50 sections, each section contains two-syllable English words. Each word in the pair will have a similar sound. By carefully listening to the words, the students will discern whether the pair of words has the same or different sound. The findings show that the ability in pronouncing two-syllable English words of eight grade students of SMPN 1 Kampar, the students’ ability is on the good level with 68 percentage. But if we look at the schools minimum passing criteria with 80 score only 30% students who can pass it. This is a very bad condition because if less than 50% students can reach the minimum passing criteria then learning can be said unsuccessful. This is caused by the lack of listening and pronunciation practice carried out at school. However, the students are suggested to engage in additional practice and exercises in order to enhance their ability to speak with proper pronunciation. Furthermore, the teachers are expected to be able to provide better teaching and learning to improve students’ pronounciation abilities.Key Words: Discovering, Pronounciation Ability, Two-Syllable Words